«Тлумачна палея» в інтерпретації Івана Франка - Борщ, С. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is devoted to the analysis of the peculiarities of I. Franko’s interpretation of ancient apocrypha – «Tlumachna paleja». Divergences in I. Franko’s and other scientists’ opinion about problems of the author, date and place where «Tlumachna paleja» was written/compiled are shown. The peculiarities of composition, source base are examined.